Determination of Domperidone and Omeprazole in Capsule Dosage form by UV/Visible Spectrophotometer - Pandey, V.P.; Vanjinathan, S.; Singh, Stella (Asian Journal of Chemistry, 2010)
In the present study, validation of quantitation of domperidone and omeprazole present in capsule formulation is carried out by using UV-visible spectrophotometry. According to ICH guidelines, the developed method was studied for specificity, accuracy, linearity, range precision, robustness and ruggedness. Determination of stability of the drugs in solution during analysis was studied. It was found that developed method obeyed Beer's law at two compound method. The concentration range of 5-10 μg/mL for domperidone and 2-10 μg/mL for omeprazole was suitable. The absorbance should be taken before 1 h due to stability reasons. The method is rapid, economic and meet ICH requirements for an analytical method for the quantification of drugs in a formulation.